PENGARUH SIKAP, NORMA SUBJEKTIF DAN PERCEIVED BEHAVIOR CONTROL TERHADAP INTENSI GURU KELAS BAWAH SEKOLAH DASAR/MADRASAH IBTIDAIYAH DALAM MENERAPKAN PEMBELAJARAN TEMATIK DI SEKOLAH DASAR NEGERI/MADRASAH IBTIDAIYAH NEGERI SE-KOTA MALANG - Inayati, Isna Nurul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2016)
Thematic learning approach has been put in place inSD/MI for about 7 years, but until now has not revealed realresults. Though starting in 2014/2015 approach to lessonslearning in SD/MI will turn into thematic integrative. To optimizethe application of this learning model, then needed a studyregarding the implementation of thematic learning in the yearsbefore. On the basis of this is the researchers trying to unravelhow the psychological condition of the master class under theSD/MI in implementing thematic study covering variableattitudes, subjective norms, perceived behavior control, andlower class teacher intensi SD/MI, this research uses aquantitative approach to the type of korelasional. The datacollected with a questionnaire with the number of respondents115 master class under the SD/MI who teaches at SDN/MIN seMalang. The data obtained are then analyzed using descriptivestatistics, correlation pearson product moment, one-wayANOVA, and multiple regression. Based on the known analysistools that are only partial variable positive influence attitudestowards intensi. While simultaneously third variable has apositive influence towards intensi, with the most dominant factoris attitude. Both of these research results are indeed a bitcontradictory. This is because according to the theory ofplanned behavior, the third application to be free variables inone unit, meaning that it can not be separated from one another